Islamic Law and Human Rights: Convergence or Conflict? - Zumiyati Sanu Ibrahim; Karimullah, Suud Sarim; Sulastri; Yavuz Gönan; Hüseyin Okur (Nurani, 2024)
The background of this study is rooted in the significance of human rights as a universal principle, which often faces challenges when applied within the context of Islamic law. The main issue is the incompatibility between some practices of Islamic law and the principles of human rights, which raises the question of how these two legal systems can interact without compromising their fundamental values. This study aims to explore the relationship between Islamic law and human rights, understand the challenges arising from differences in interpretation and implementation, and offer solutions to bridge these differences. This study uses a qualitative method combining text analysis, literature, and secondary data better to understand the concept of human rights in Islam and identify areas of potential conflict. The results show that the relationship between Islamic law and human rights is complex, where potential conflicts and convergence efforts coexist. Despite potential conflicts, the values of justice, equality, and human dignity in Islam align with Human Rights principles. However, differences in interpretation and implementation of the law can be a significant source of tension. This study highlights the importance of an approach rooted in cross-cultural and religious dialogue, as well as respect for diversity, to achieve a more harmonious convergence between Islamic law and universal human rights.